Formation of H+ PUI Tails Downstream of Distant Interplanetary Shocks - E. J. Zirnstein; D. J. McComas; B. L. Shrestha; H. A. Elliott; P. C. Brandt; S. A. Stern; A. R. Poppe; J. Parker; E. Provornikova; K. Singer; A. Verbiscer; New Horizons Heliophysics Team (The Astrophysical Journal)
New Horizons’ Solar Wind Around Pluto (SWAP) instrument has observed interplanetary shocks from ∼20 to 60 au from the Sun. Different studies have analyzed the effects of these shocks on the solar wind ion (SWI) and interstellar pickup ion (PUI) distributions. A key finding includes the observation of PUI tails downstream of some shocks. However, PUI tails have only been observed when SWAP was measuring 24 hr averages of the count rate histograms. After a software change in 2021 February, SWAP’s measurement resolution was improved to ∼30 minutes averages, but no PUI tails have been observed since this change. In this study, we use a test particle code to simulate the downstream SWI and PUI distributions to study the possible existence and formation of PUI tails, using the shock compression ratio, shock thickness, and turbulence as free parameters. We find that in most cases, a suprathermal tail does not develop downstream of interplanetary shocks, but a persistent hump and PUI cutoff exists at energies above the PUI injection energy. The extent of the hump largely depends on the shock compression ratio. We find PUI tails do form when turbulence is included in the model. After we convert our distributions to count rates in the spacecraft frame, the results show similar structure to the data. We conclude that significant H ^+ PUI tails can form downstream of distant interplanetary shocks if there is a relatively large compression ratio (>2) and significant turbulence present.